2018
DOI: 10.1111/jdi.12857
|View full text |Cite
|
Sign up to set email alerts
|

Disease duration as an indicator of the efficacy of liraglutide in patients with type 2 diabetes mellitus

Abstract: Comment on the article of Usui et al. Retrospective cohort study of obese patients with type 2 diabetes mellitus (n = 69) demonstrates that the glucose‐lowering effect of liraglutide as add on therapy to insulin relies on the remaining beta‐cell function in type 2 diabetes. Shorter disease duration implies a more favourable prognosis for response on instantaneous substitution of insulin with liraglutide (HR 2.39 (95% CI: 1.20–4.76).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These findings suggest that in patients with relatively long duration of diabetes, GLP-1 RAs could be an effective treatment option. However, previously it was reported that in patients treated with liraglutide uncontrolled on insulins, the glucose-lowering effect depends on the duration of diabetes and beta-cell function [ 16 , 17 ]. In our study, the glucose-lowering effect did not vary based on duration of diabetes, which could be due to differences in study design and patient population.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that in patients with relatively long duration of diabetes, GLP-1 RAs could be an effective treatment option. However, previously it was reported that in patients treated with liraglutide uncontrolled on insulins, the glucose-lowering effect depends on the duration of diabetes and beta-cell function [ 16 , 17 ]. In our study, the glucose-lowering effect did not vary based on duration of diabetes, which could be due to differences in study design and patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may suggest an added value of weight loss on glucose reduction in patients with T2D and overweight or obesity. In this study, a significantly greater reduction in HbA1c and SMBG profile was observed in younger patients receiving tirzepatide 15 mg. Interestingly, a previous study in patients with uncontrolled T2D on insulin showed that the glucose-lowering effect of liraglutide was dependent on beta cell function [ 19 , 20 ]. However, we observed that blood glucose control, including reductions in HbA1c, FSG and SMBG profiles, was similar across the three tirzepatide treatment groups by duration of T2D (< 10 vs. ≥ 10 years), which is consistent with the results of a previous subgroup analysis from the global phase 3 SURPASS studies that investigated the glycemic effect of tirzepatide by duration of diabetes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible role of Gal-3 as a predictor of successful therapy in patients with T2DM has been previously discussed [ 44 ]. Since liraglutide seems most effective in patients with the highest remaining β‐cell function [ 45 , 46 ] our hypothesis is that low basal Gal-3 levels may serve as biomarkers to identify this subset of patients. This is supported by a recent experimental model of obesity-induced diabetogenesis, showing that Gal-3 overexpression facilitates β-cell damage, enhances oxidative stress and beta-cell apoptosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%